Probability teaching in the training of Faculdade de Ciências e Tecnologia Dirson Maciel de Barros (FADIMAB) pedagogues (Research, Society and Development, 2024)
This article deals with a study that aimed to investigate the knowledge about the probability of a group of 45 students from the FADIMAB pedagogy course. A social survey was carried out and data collection took place through the application of a questionnaire with 12 structured questions (YES and No), aiming to characterize knowledge about probability in the undergraduate course in Pedagogy, offered by FADIMAB located in Goiana in Zona da Mata Norte. The data collected revealed the need to include disciplines and proposals that promote the study of concepts of probability combined with didactic-pedagogical training in the Pedagogy curriculum. Therefore, the National Common Curricular Base (BNCC) positions probability as one of the themes to be explored in the teachng of Mathematics throughout basic education, from the early years to high school. This ensures that students gradually become familiar with probabilistic concepts according to their age and level of cognitive development. It addresses probability within the area of Mathematics, providing guidelines for its teaching. It should be noted that it is urgent and essential to develop, with future teachers, a continuing training program on this topic.